What is Culture? Kant and Simmel - Kyslan, Peter (Con-Textos Kantianos. International Journal of Philosophy, 2016)
Immanuel Kant and Georg Simmel both lived in different cultural atmospheres. While the former is the one who reflects upon the enlightenment era with criticism and hope, the latter evaluates capitalism and the industrial era with apathetic criticism. However, both of them have managed to philosophically grasp the phenomenon of culture in its universality and true meaning. This text aims at identifying the parallels between the spirits of both eras.